Opening the Door: Ruth Bader Ginsburg, Law’s Boundaries, and the Gender of Opportunities - Resnik, Judith (Columbia Journal of Gender and Law, 2013)
A pervasive assumption is that nation-states have bounded legal regimes. Yet the burdens imposed on women in the name of gender and sexuality have not been circumscribed by jurisdictional lines. Rather, gender hierarchies have traveled-by way of Roman law, civil law, the common law, and religious systems-to impose constraints on women living under autocracies, republican democracies, and other political forms. The many laws supporting gender inequalities make plain that legal rules internal to a nation-state are often not indigenous to a particular polity but, instead, are regularly shaped by cross-border influences. Similarly, efforts to interrupt inequalities know no jurisdictional bounds. In tension with the classical model of state-to-state international law production, human rights movements of this and of other eras result from diverse exchanges across jurisdictional hierarchies. Illustrative are the equality projects of earlier centuries-emancipation for slaves and equality for women of all colors-that spanned oceans through networks of local religious and secular societies communicating (before the internet) via the post, pamphleteering, and the press to demand legal reforms. Indeed, one can understand women’s groups as the original “NGOs”-organizations that were nongovernmental not by choice but by exclusion and yet remarkably generative.